METHODOLOGY OF AHL SUNNAH WAL JAMAAH TO OVERCOME THE CONFUSION ON CONCEPT OF MUKHALAFATUHU LIL HAWADITH - Alwi, Engku Ahmad Zaki Engku; Basri, Muhammad Nasri Hassan; Shuhari, Mohd Hasrul; Wok Zin, Engku Ibrahim Engku; Hamat, Mohd Fauzi; Mohd Yazid, Nur Solehah (International Journal of Psychosocial Rehabilitation, 2020)
The confusion of concepts ‘Mukhalafatuhu lil Hawadith’ was seen as the main cause for ‘Firaq Islamiyyah’ among the Muslims who fails to understand Aqidah al-Islamiyyah from the perspective of Ahli Sunnah wal Jama’ah’s view. One of the elements of the Islam perspective is to understand in god and to accept these elements important to understand thoroughly the concept Mukhalafatuhu li al-Hawaadith. Thus, the objective of this study was to analyse the methodology of Ahl Sunnah wal Jama’ah’s scholars in this concept and able to be a solution to overcome the confusion. In this study, researchers conducted a study descriptive qualitative to collect and analyse the data. Besides that, the study also recognises the methodology that has been taken by the scholars of Ahli Sunnah Wal Jama’ah to solve and overcome the confusion that related with the concept of Mukhalafatuhu lil Hawadith in faiths.